Prevalence and Determinants of Hypertension Among Urban School Teachers in Patna, India - Kumar, Vikash; Dharmvir Ranjan Bharati; Prasad, Nidhi; Kumar, Sanjay (National Journal of Community Medicine, 2024)
Background: Hypertension, a major cause of cardiovascular disease, is increasingly common among urban professionals, including school teachers, who face unique stressors and lifestyle challenges. Understanding these factors is essential for developing targeted health interventions. This study aims to determine the prevalence and key determinants of hypertension among government school teachers in Patna. Methodology: A cross-sectional survey was conducted from November 2021 to October 2022 with 1321 teachers from 325 urban schools in Patna. The sample size was calculated based on a 45.4% estimated hypertension prevalence, with a 3% margin of error and 20% non-response rate. Teachers were selected using stratified sampling with probability proportional to size. Results: Of the 1283 respondents, 61.34% were male and 38.66% female. The overall prevalence of hypertension was 14.1%, higher in males (15.5%) than females (11.9%). Hypertension was significantly associated with frequent fast-food consumption, extra salt intake, tobacco use, stress, and higher BMI (p<0.05), though not with age, gender, physical activity, or depression. Conclusions: Improving dietary habits, reducing tobacco use, and managing BMI among teachers can significantly reduce hypertension. Healthier teachers create a better teaching environment, positively impacting student learning outcomes and enhancing the overall educational experience.